Net baryon production in the CGC formalism. (July 2015) - Duraes, F O; Giannini, A V; Goncalves, V P; Navarra, F S
Abstract: In this work the net-baryon production at forward rapiditiesis investigated considering the CGC formalism. We assume that at large energies the coherence of the projectile quarks is lost and that the leading baryon production mechanism changes from recombination to independent fragmentation. The phenomenological implications for net-baryon production in pp/pA/AA collisions are analyzed and predictions for LHC energies are presented. We also extend previous studies to pp and pA collisions and estimate for the first time the nuclear modification ratio, equal to the ratio of the net-proton production cross section in pA collisions over the one in pp collisions, scaled by the number of binary collisions, for leading baryon production.